2017
DOI: 10.3389/fpls.2017.01392
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in Relation to Vigor and Viability of White Lupin (Lupinus albus L.) Seed Stored for 26 Years

Abstract: The aim of the study was to evaluate the vigor and viability as well as to determine and compare the contents of selected protein fractions of white lupin (Lupinus albus L.) seeds stored for 26 years at temperatures of -14°C and +20°C. The seeds stored at -14°C germinated in 86.3%, while the seeds stored at +20°C did not germinate at all. The viability evaluation was confirmed by the measuring electroconductivity of seed exudates. In seeds stored at -14°C the contents of γ, δ, and β conglutin were 14, 4 and 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Data presented here demonstrated higher germination proportion in wild annual Lupinus relative to wild perennial congeners. Similarly high germination has been observed in other studies of annual Lupinus species (Schaal, 1980; including in L. albus after 26 years in frozen storage, Dobiesz & Piotrowicz-Cieslak, 2017), and similarly low germination proportion has been observed in other perennial western North American Lupinus species (Greipsson & El-Mayas, 2003; Sõber & Ramula, 2013). Pitelka (1977) found that while North American herbaceous perennials had somewhat higher germination than annual Lupinus in field sites, both groups had less than 40% germination.…”
Section: Discussionsupporting
confidence: 84%
“…Data presented here demonstrated higher germination proportion in wild annual Lupinus relative to wild perennial congeners. Similarly high germination has been observed in other studies of annual Lupinus species (Schaal, 1980; including in L. albus after 26 years in frozen storage, Dobiesz & Piotrowicz-Cieslak, 2017), and similarly low germination proportion has been observed in other perennial western North American Lupinus species (Greipsson & El-Mayas, 2003; Sõber & Ramula, 2013). Pitelka (1977) found that while North American herbaceous perennials had somewhat higher germination than annual Lupinus in field sites, both groups had less than 40% germination.…”
Section: Discussionsupporting
confidence: 84%
“…6c, Supplementary Data 14), which are precursor forms normally synthesized in developing cotyledons to give rise to mature polypeptides of lower molecular weight. Their degradation starts as part of the germination process and the appearance of simpler forms in the domesticated variety AMIGA could be linked with its increased seed vigor 44 . The long chain ß-conglutins present in the wild accession is also associated with a high allergenicity of lupin seeds 45 Measurement of the abundance of key alkaloids in various organs revealed that the modern accession AMIGA has very low levels of lupanine, 13-hydroxylupanine and 13-tigloyloxylupanine ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above-ground parts of pea seedlings were ground to a powder in liquid nitrogen. Protein isolation and separation by the 2D electrophoresis method was carried out according to Dobiesz and Piotrowicz-Cieślak [30]. The peptide separation and determination of peptide masses was carried out using the Orbitrap spectrometer (Thermo).…”
Section: Methodsmentioning
confidence: 99%